Pyrenophora teres: Profile of an increasingly damaging barley pathogen - Zhaohui, L.; Ellwood, Simon; Oliver, Richard; Friesen, T. (Wiley-Blackwell Publishing Ltd., 2011)
Pyrenophora teres, causal agent of net blotch of barley, exists in two forms, designated P. teres f. teres and P. teres f. maculata, which induce net form net blotch (NFNB) and spot form net blotch (SFNB), respectively. Significantly more work has been performed on the net form than on the spot form although recent activity in spot form research has increased because of epidemics of SFNB in barley‐producing regions. Genetic studies have demonstrated that NFNB resistance in barley is present in both dominant and recessive forms, and that resistance/susceptibility to both forms can be conferred by major genes, although minor quantitative trait loci have also been identified. Early work on the virulence of the pathogen showed toxin effector production to be important in disease induction by both forms of pathogen. Since then, several laboratories have investigated effectors of virulence and avirulence, and both forms are complex in their interaction with the host. Here, we assemble recent information from the literature that describes both forms of this important pathogen and includes reports describing the host–pathogen interaction with barley. We also include preliminary findings from a genome sequence survey.